Deciphering the interaction between N-palmitoyl-D-glucosamine and the endocannabinoidome - Aniello Schiano Moriello; Marco Allarà; Fabio Arturo Iannotti; Gabriele Marcolongo; Fabiana Piscitelli; Roberta Verde; Vincenzo Di Marzo; Stefania Petrosino (Scientific Reports)
Abstract N-palmitoyl-D-glucosamine (PGA) belongs to the class of molecules known as Autacoid Local Injury Antagonism (ALIA)-amides, whose parent compound is N-palmitoyl-ethanolamine (PEA) an endocannabinoid-like mediator belonging to the expanded endocannabinoid system (the endocannabinoidome). The mechanism of action of ALIA-amides is mainly targeted at the down-regulation of the hyperactivity of peripheral mast cells and non-neuronal cells of the central nervous system. This study aimed to investigate if PGA is able to produce the typical “entourage” effect of PEA, consisting of increasing the endogenous levels of the endocannabinoids anandamide (AEA) and 2-arachidonoylglycerol (2-AG), and to also elevate endogenous PEA levels. PGA (10 µM) treatment of HaCaT cells for 40 min and 6 h resulted in higher cellular concentrations of AEA, 2-AG and PEA. The increase of endocannabinoid and PEA levels was observed both after 40 min and 6 h of PGA treatment. The unselective serine hydrolase inhibitor MAFP (10 µM) inhibited the PGA-induced increase in cellular concentrations of AEA, 2-AG and PEA. The mRNA expression of endocannabinoid and PEA anabolic (NAPEPLD, ABHD4, GDE1, DAGLA and DAGLB) and catabolic (FAAH, MAGL and NAAA) enzymes was also measured, revealing a significative reduction of GDE1, DAGLB, FAAH, MAGL and NAAA, after PGA treatment for 6 h. Finally, AEA, 2-AG and PEA were also measured in HaCaT cells after siRNA against ABHD4 and PGA treatment for 40 min, revealing an increase of their endogenous levels. In conclusion, we demonstrated for the first time that PGA increases PEA and endocannabinoid levels, thus potentially strengthening a part of endocannabinoidome signaling.